Vitamin C Content in Tropical Fruits and Vegetables Available in Different Districts of Bangladesh (Journal of Bangladesh Academy of Sciences, 2010)
DOI: 10.3329/jbas.v33i2.4107 Journal of Bangladesh Academy of Sciences, Vol. 33, No. 2, 231-234, 2009